2013
DOI: 10.1016/j.crci.2013.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Xanthan sulfuric acid: An efficient and biodegradable solid acid catalyst for the synthesis of bis(indolyl)methanes under solvent-free conditions

Abstract: Xanthan sulfuric acid (XSA) is found to be an efficient catalyst for the electrophilic substitution reaction of indole with aromatic aldehydes to afford the corresponding bis(indolyl)methanes at room temperature under solvent-free conditions. The catalyst was characterized for the first time with the help of powder XRD, SEM-EDX and DSC-TGA. The attractive features of this green, new methodology are excellent yield of products, clean reaction profile, reusability of the catalyst, energy sustainable protocol, si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…The most common examples in literature for the reaction of the synthesis of BIMs under solvent-free conditions utilize either protic acids, such as camphorsulfonic acid (CSA) [44], diammonium hydrogen phosphate (DAHP) [45], Amberlyst 15 [46], P 2 O 5 /MeSO 3 H [47], p-sulfonic acid calix [4]arene [48], xanthan sulfuric acid (XSA) [49], H 5 PW 10 V 2 O 40 /pyridinosanta barbara amorphous-15 (SBA-15) [50], TiO 2 -SO 4 2− [51,52], humic acid [53] or Lewis acids, such as N-bromosuccinimide (NBS) [54], silica chloride [55], Ph 3 CCl [56], ZnO [57], La(NO 3 ) 3 •6H 2 O [58], V(HSO 4 ) 3 [59], Cu(ClO 4 ) 2 •6H 2 O [60], Fe/Al pillared clay [61], trimethylsilyl chloride (TMSCl) [62], BiCl 3 -loaded montmorillonite K10 [63][64][65][66][67], ZrO 2 -MgO [68] or CaO [69]. Silica gel is an intriguing solid support, since it is a low cost, commercially available and non-hazardous support, that can be employed in tandem with various traditional catalysts [70].…”
Section: Green and Sustainable Approachesmentioning
confidence: 99%
“…The most common examples in literature for the reaction of the synthesis of BIMs under solvent-free conditions utilize either protic acids, such as camphorsulfonic acid (CSA) [44], diammonium hydrogen phosphate (DAHP) [45], Amberlyst 15 [46], P 2 O 5 /MeSO 3 H [47], p-sulfonic acid calix [4]arene [48], xanthan sulfuric acid (XSA) [49], H 5 PW 10 V 2 O 40 /pyridinosanta barbara amorphous-15 (SBA-15) [50], TiO 2 -SO 4 2− [51,52], humic acid [53] or Lewis acids, such as N-bromosuccinimide (NBS) [54], silica chloride [55], Ph 3 CCl [56], ZnO [57], La(NO 3 ) 3 •6H 2 O [58], V(HSO 4 ) 3 [59], Cu(ClO 4 ) 2 •6H 2 O [60], Fe/Al pillared clay [61], trimethylsilyl chloride (TMSCl) [62], BiCl 3 -loaded montmorillonite K10 [63][64][65][66][67], ZrO 2 -MgO [68] or CaO [69]. Silica gel is an intriguing solid support, since it is a low cost, commercially available and non-hazardous support, that can be employed in tandem with various traditional catalysts [70].…”
Section: Green and Sustainable Approachesmentioning
confidence: 99%
“…Siddiqui and Tarannum introduced an eco-friendly approach for the synthesis of pyrazole-containing bis(indolyl)methane derivatives (289 a,b) in excellent yields via the electrophilic substitution reaction of an indole (232) with substituted pyrazole-4-carbaldehydes (288 a,b) in the presence of xanthan sulfuric acid (XSA) as a catalyst under solvent-free (grinding) conditions (Scheme 50). [99] Catalyst reusability, pollution-free reaction profile, energy sustainability, inexpensive catalyst, and easy purification of the product are the major attractions of this methodology. Similarly, Murugan et al reported the synthesis of various bis(indolyl)pyrazolyl methanes (292 a-j) utilizing chloroplatinic acid (H 2 PtCl 6 ) as a catalyst in ionic liquid (1-butyl-3-methylimidazolium chloride, [bmim]Cl) as well as heteropoly acid (H 4 [Si(W 3 O 10 ) 3 ]) as the catalyst in acetonitrile (Scheme 50).…”
Section: Methane-linked Bis-indole-c3 Pyrazole Hybridsmentioning
confidence: 99%
“…Siddiqui and Tarannum introduced an eco‐friendly approach for the synthesis of pyrazole‐containing bis(indolyl)methane derivatives ( 289 a , b ) in excellent yields via the electrophilic substitution reaction of an indole ( 232 ) with substituted pyrazole‐4‐carbaldehydes ( 288 a , b ) in the presence of xanthan sulfuric acid (XSA) as a catalyst under solvent‐free (grinding) conditions (Scheme 50). [99] Catalyst reusability, pollution‐free reaction profile, energy sustainability, inexpensive catalyst, and easy purification of the product are the major attractions of this methodology. Similarly, Murugan et al.…”
Section: Spacer‐linked Indole‐c3 Pyrazole Hybridsmentioning
confidence: 99%
“…Siddiqui and co-workers 56 have developed a solvent free procedure for the synthesis of bis(indolyl)methanes by using indole and aromatic aldehydes in the presence of xanthan sulfuric acid (XSA) by grinding at room temperature to afford the products in high yield (Scheme 26). Various catalysts such as zinc acetate, NiCl 2 , AlCl 3 , benzenesulfonic acid, sulfuric acid, sulfamic acid, L-proline and Zn(L-proline) 2 were employed in this reaction in a comparative study; however, they did not give good results.…”
Section: Synthesis Of Bis(indolyl)methane Derivativesmentioning
confidence: 99%